Unveiling Myanmar Dropout High School Students' Motivation in EFL Learning Based on Self-Determination Theory - Kyaw, Chaw Chaw Ei; Wilang, Jeffrey Dawala (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2025)
This study examines the role of motivation based on the Self-Determination Theory (SDT) among Myanmar high school dropout students who continue learning English. Specifically, it explores the underlying motivational factors and their impact on students' engagement with EFL learning. The study involved nine Myanmar high school dropout students who have attended or are currently attending EFL centers in different cities. Data were collected through online and face-to-face interviews, focusing on students' experiences in learning English. Findings indicated that motivation in EFL learning is driven by inner spark, doors of opportunity, and loss of momentum in formal education, alongside the SDT elements of pursuing a purposeful path, empowerment through growth, connections, and expanding aspirational horizons. The results also suggest that students exhibit a high degree of autonomous motivation in their learning and develop stronger social engagement compared to their previous educational experiences. Additionally, while some students are motivated to pursue further education, others express a strong desire to contribute to their communities. Overall, the study highlights that high school dropout students in Myanmar demonstrate motivation to learn English, both to achieve personal goals and to contribute to their society. These findings underscore the need for socio-cultural, metacognitive, and technology-enhanced teaching approaches tailored to the autonomous learning styles of these students